Meloidogyne enterolobii reproduction on vegetable crops and plants used as green manure - Osorio Rosa, Juliana Magrinelli [UNESP]; Westerich, Juliana Nogueira [UNESP]; Siciliano Wilcken, Silvia Renata [UNESP] (Univ Federal Ceara, Dept Geol, 2015)
Meloidogyne enterolobii is considered to be an aggressive root-knot species. The goal of this work was determine the M. enterolobii reproduction factor on 42 vegetable crops and on 18 plants used as green manure. The experiments were carried in a greenhouse. The substrate inoculation was made with 5,000 eggs and second stage juveniles of M. enterolobii/plot. The experimental delineations were entirely randomized, with six replications. Resistance was found in 'Brasilia', 'Brasilia Irece' and 'Planeta' carrot, 'Grand Rapids' lettuce; 'Tokyo' and 'Nebuka' chive; 'Poro Gigante' leeks; 'Comum HT' and 'Grauda Portuguesa' parsley and all brassicas plants studied: 'Teresopolis Gigante' and 'Piracicaba Precoce' cauliflower; 'Chato de Quintal' and 'Coracao de Boi' cabbage; 'Piracicaba', 'Brasilia', 'Santana' and 'Cabeca' broccoli and 'Bruxelas' and 'Tronchuda Portuguesa' cole. Lollium multiflorum, Crotalaria breviflora, C. juncea, C. spectabilis, C. mucronata, C. ochroleuca, Dolichos lablab, Pennisetum glaucum, Mucuna deeringiana, M. cinereum, M. aterrima and Raphanus sativus green manures were resistant. These plants are viable options to crop rotation in M. enterolobii infested areas.
Keywords: Root-knot nematodes; Horticultural; Green manure